Sharia and State’s Intervention: Uncertainty Cryptocurrency in Indonesia - Asep Syarifuddin Hidayat (AHKAM : Jurnal Ilmu Syariah, 2023)
Cryptocurrencies have gained significant attention as part of global economic developments, prompting serious considerations from governments as public financial authorities. The current response to cryptocurrencies goes beyond their role as a form of currency and extends to their classification as assets. This study aims to analyze Indonesia's governmental policies concerning cryptocurrencies, explicitly examining their compliance with sharia principles regarding their classification as both currency and investment. The research methodology employed in this study is a primarily normative legal analysis, relying on legislative regulations, fatwas issued by the Indonesian Ulama Council (MUI), and the Fatwa Council of the Central Executive Board of Muhammadiyah. Through this normative approach, the study reveals that cryptocurrencies possess inherent instability, distinguishing them from stable currencies. Consequently, their uncontrolled nature makes it challenging for governments to regulate them effectively during periods of inflation and deflation. State intervention, therefore, is limited to acknowledging cryptocurrencies as assets rather than recognizing them as official currencies. However, this governmental recognition of cryptocurrencies as assets contradicts the fatwa issued by the MUI, which asserts that cryptocurrencies fail to meet syurūṭ al-sil'ah fī al-mabā'i, primarily due to their lack of precise value and quantity. Moreover, cryptocurrencies can be categorized as forms of hoarding (iḥtikār) and uncertainty (gharar), both of which are considered contrary to the objectives of maqāṣid al-sharī'ah.  Abstrak: Cryptocurrency sebagai bagian dari perkembangan baru ekonomi global mendapatkan perhatian serius dari negara sebagai otoritas keuangan publik. Respon terhadap cryptocurrency sekarang ini tidak hanya berkisar pada posisinya sebagai mata uang, tetapi juga sebagai aset. Studi ini menganalisis kebijakan negara Indonesia terhadap cryptocurrency yang dihubungkan dengan posisi syariat Islam terhadap cryptocurrency sebagai mata uang dan aset. Studi ini dilakukan dengan penelitian hukum normatif, yang bersumber dari peraturan perundang-undangan, fatwa Majelis Ulama Indonesia (MUI) dan Majelis Tarjih dan Tajdid Pengurus Pusat Muhammadiyah. Dengan pendekatan normatif, studi ini menemukan bahwa cryptocurrency memiliki nilai instabilitas yang berbeda dengan konsep mata uang yang bersifat stabil. Hal ini menjadikan cryptocurrency sulit dikendalikan oleh negara ketika terjadi inflasi dan deflasi. Intervensi negara hanya sebatas mengakuinya sebagai aset, bukan sebagai mata uang. Pengakuan negara terhadap cryptocurrency sebagai aset bertentangan dengan fatwa MUI yang menyatakan bahwa cryptocurrency tidak memenuhi syurūṭ al-sil’ah fī al-mabā'i, tidak memiliki nilai dan jumlah yang pasti. Lebih dari itu, cryptocurrency dapat dikategorikan sebagai iḥtikār dan gharar yang bertentangan dengan maqāṣid al-sharī'ah.